Morphology of human sinoatrial node and its surrounding right atrial muscle in the global obesity pandemic—does fat matter? - Chen, Weixuan; Rams, Daniel; Zając, Maciej; Albalawi, Raghad; Atkinson, Andrew J.; Aminu, Abimbola J.; Mazur, Malgorzata; Hołda, Mateusz K.; Walocha, Jerzy; Gil, Krzysztof; Kuniewicz, Marcin; Dobrzynski, Halina (Frontiers in Medicine, 2024)
Introduction The sinus node (SN) is the main pacemaker site of the heart, located in the upper right atrium at the junction of the superior vena cava and right atrium. The precise morphology of the SN in the human heart remains relatively unclear especially the SN microscopical anatomy in the hearts of aged and obese individuals. In this study, the histology of the SN with surrounding right atrial (RA) muscle was analyzed from young non-obese, aged non-obese, aged obese and young obese individuals. The impacts of aging and obesity on fibrosis, apoptosis and cellular hypertrophy were investigated in the SN and RA. Moreover, the impact of obesity on P wave morphology in ECG was also analyzed to determine the speed and conduction of the impulse generated by the SN. Methods Human SN/RA specimens were dissected from 23 post-mortem hearts (preserved in 4% formaldehyde solution), under Polish local ethical rules. The SN/RA tissue blocks were embedded in paraffin and histologically stained with Masson’s Trichrome. High and low-magnification images were taken, and analysis was done for appropriate statistical tests on Prism (GraphPad, USA). 12-lead ECGs from 14 patients under Polish local ethical rules were obtained. The P wave morphologies from lead II, lead III and lead aVF were analyzed. Results Compared to the surrounding RA, the SN in all four groups has significantly more connective tissue (P ≤ 0.05) (young non-obese individuals, aged non-obese individuals, aged obese individuals and young obese individuals) and significantly smaller nodal cells (P ≤ 0.05) (young non-obese individuals, aged non-obese individuals, aged obese individuals, young obese individuals). In aging, overall, there was a significant increase in fibrosis, apoptosis, and cellular hypertrophy in the SN (P ≤ 0.05) and RA (P ≤ 0.05). Obesity did not further exacerbate fibrosis but caused a further increase in cellular hypertrophy (SN P ≤ 0.05, RA P ≤ 0.05), especially in young obese individuals. However, there was more infiltrating fat within the SN and RA bundles in obesity. Compared to the young non-obese individuals, the young obese individuals showed decreased P wave amplitude and P wave slope in aVF lead. Discussion Aging and obesity are two risk factors for extensive fibrosis and cellular hypertrophy in SN and RA. Obesity exacerbates the morphological alterations, especially hypertrophy of nodal and atrial myocytes. These morphological alterations might lead to functional alterations and eventually cause cardiovascular diseases, such as SN dysfunction, atrial fibrillation, bradycardia, and heart failure.